Intratympanic Corticosteroid Salvage for Pediatric Bilateral Sudden Sensorineural Hearing Loss Complicated by Methylprednisolone-Induced Hypertensive Urgency in an Obese Adolescent - Jihan Mudrika Rahmi; Rossy Rosalinda (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Bilateral sudden sensorineural hearing loss (SSNHL) is a rare otologic emergency, accounting for less than 5% of sudden deafness cases and occurring even less frequently in pediatric populations. Unlike unilateral cases, bilateral involvement strongly implicates systemic etiologies such as autoimmune inner ear disease (AIED). Systemic high-dose corticosteroids are the standard first-line therapy but pose significant risks of toxicity, including hypertensive crisis, particularly in adolescents with metabolic risk factors. Case presentation: We report the case of a 17-year-old male (BMI 29.0 kg/m²) presenting with acute, simultaneous bilateral hearing loss (Pure Tone Average [PTA]: Right 82.5 dB, Left 81.25 dB) and severe tinnitus (Tinnitus Handicap Index [THI]: 78). Initial management with high-dose intravenous methylprednisolone (500 mg/day) was complicated on Day 7 by hypertensive urgency (Blood Pressure 150/95 mmHg) and neurological symptoms, necessitating immediate cessation of systemic therapy. Diagnostic investigation was limited by resource availability; however, elevated inflammatory markers supported a presumptive immune-mediated etiology. A salvage protocol was initiated using four weekly cycles of intratympanic Triamcinolone Acetonide. Following therapy, the patient demonstrated slight audiological recovery (PTA stabilized at 65 dB bilaterally) but achieved complete resolution of tinnitus (THI: 0). Conclusion: This case highlights the critical role of intratympanic corticosteroids as a safe salvage modality when systemic therapy is contraindicated due to toxicity. The dissociation between modest audiometric gain and complete tinnitus resolution suggests successful mitigation of cochlear synaptopathy. The case underscores the necessity of cardiovascular monitoring and BMI-adjusted risk stratification in adolescents receiving high-dose steroids.